Influence of electron irradiation on the structure evolution and creep of Zr1Nb alloy at 380 °C - Karaseva, E.V.; Malykhin, S.V.; Mats, A.V.; Mats, V.A.; Savchuk, E.S.; Sokolenko, V.I. (Вопросы атомной науки и техники, 2021)
The effect of electron irradiation on the evolution of the structure and creep of the samples Zr1Nb alloy of industrial production and samples obtained by the IPD method were studied. It was shown that irradiation with electrons with a dose not exceeding D = 5∙10¹⁹ сm⁻² does not affect the plastic deformation mechanisms of the industrial Zr1Nb alloy, as a result of which its high thermomechanical and radiation stability is maintained. Irradiation by electrons with an energy of E = 10 MeV and doses of D = 6∙10¹⁷ and 5∙10¹⁹ сm⁻² does not change the character of the deformation nanostructure of the Zr1Nb alloy, but initiates return processes in grain boundaries and boundary regions and cause the changes in crystalline anisotropy of GPU lattice, which leads to softening of the material during creep at 380 °C.